2017
DOI: 10.1002/hbm.23645
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale network organization of EEG functional connectivity in newborn infants

Abstract: The organization of functional brain networks changes across human lifespan. The present study analyzed functional brain networks in healthy full-term infants (N = 139) within 1-6 days from birth by measuring neural synchrony in EEG recordings during quiet sleep. Large-scale phase synchronization was measured in six frequency bands with the Phase Lag Index. Macroscopic network organization characteristics were quantified by constructing unweighted minimum spanning tree graphs. The cortical networks in early in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 73 publications
4
66
0
Order By: Relevance
“…The smaller Diameter and larger Leaf Fraction in children compared to adults indicates that the topology of the functional brain networks becomes segregated via a transition from a star-like (centralised) configuration toward a more line-like (de-centralised) configuration during development. Such network topological change has been found in infants right after birth ( Toth et al, 2017 ) and continues up to 18 years of age ( Boersma et al, 2011 ). In addition, the observed larger Kappa in children compared to adults suggests a movement away from a scale-free network.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The smaller Diameter and larger Leaf Fraction in children compared to adults indicates that the topology of the functional brain networks becomes segregated via a transition from a star-like (centralised) configuration toward a more line-like (de-centralised) configuration during development. Such network topological change has been found in infants right after birth ( Toth et al, 2017 ) and continues up to 18 years of age ( Boersma et al, 2011 ). In addition, the observed larger Kappa in children compared to adults suggests a movement away from a scale-free network.…”
Section: Discussionmentioning
confidence: 93%
“…It follows then, that electrophysiological networks are expected to become increasingly segregated during childhood development. However, prior EEG studies have reported conflicting results, which include increasing segregation ( Boersma et al, 2011, 2013; Janssen et al, 2017; Toth et al, 2017 ), decreasing segregation ( Smit et al, 2016; Bathelt et al, 2013; Miskovic et al, 2015 ), or no changes with age ( Schafer et al, 2014 ). Discrepancy between developmental MRI-and electrophysiology-based network findings has been difficult to reconcile, partly due to the different spatial scales that functional networks have been examined at (sensor-level in most EEG versus cortical-level in fMRI studies).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although high-density EEG studies with more than 64 recording channels can display a highly spatial resolution of brain function and the number of electrodes or nodes can improve the GTA analysis, several recent studies with limited recording channels indicate that reliable results can also be obtained using standard 10/20 system with 19 EEG channels 12,13,[60][61][62][63] . In order to compute a functional brain network, we used coherence as a simple and well-studied EEG connectivity measure 4,12,14,[64][65][66][67] .…”
Section: -3 Eeg Connectivity and Adjacency Matrixmentioning
confidence: 99%
“…One study evaluated the influence of these parameters on the neural connection of neonates 33 . The objective was to evaluate the organization of functional networks of large-scale phase synchronization in brains of newborns during silent sleep and to explore their relationship with gestational age and variables that characterize possible prenatal influences on brain maturation.…”
Section: Coherence or Geodesic Sensor Net Electroencephalogrammentioning
confidence: 99%